THE EFFECT OF SUPPLY CHAIN MANAGEMENT ON SMIs OPERATIONAL PERFORMANCE (Study on Packaged Coffee Powder Industry in Sigi District) - Herman; Sulaeman Miru; Asngadi (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This research aims to determine and describe the effect of supply chain management, which consists of information sharing, long-term relationships, cooperation, and integration processes, on the operational performance of packaged coffee powder SMIs in Sigi District. This type of research was quantitative descriptive. The testing procedure usedwas census technique where the entire population was examined by 55 respondents. The types of information were quantitative and qualitative. Information sources covered essential information and optional information. Methods of collecting information were conducted through interviews, observation, questionnaires, and documentation. The data analysis technique used was multiple regression analysis. The research results show that (1) supply chain management, which consists of information sharing, long-term relationships, cooperation, and integration processes, has a positive and significant relationship to the operational performance of Packaged Coffee Powder SMIs in Sigi District. (2) Information sharing has a positive and significant relationship with the operational performance of Packaged Coffee Powder SMIs in Sigi District. (3) The long-term relationship has a negative and significant relationship to the operational performance of Packaged Coffee Powder SMIs in Sigi District. (4) Cooperation has a positive and significant relationship to the operational performance of Packaged Coffee Powder SMIs in Sigi District (5) The integration process has a positive and significant relationship to the operational performance of Packaged Coffee Powder SMIs in Sigi District.